ANALISIS MANAJEMEN FUNDRAISING WAKAF, INFAQ DAN SHODAQOH - Ilhami; Anggraini, Dian (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2022)
Fundraising management is an activity to collect waqf, infaq and shodaqoh funds through the process of planning, organizing, leading and controlling in achieving goals. In fundraising activities there are management functions and steps in carrying out these functions. Traditionally, a manager's job has been described according to the classic management functions, namely: planning, organizing, leading, and controlling. It is necessary to understand the management functions and steps of good fundraising management, including: First, the planning function which includes future calculations and forecasts, determination and formulation of targets, determination of methods, determination of time and location, and program determination, costing. Second, the organizing function in the division of tasks and responsibilities, coordination between management and the relationship between section management. Third, the function of leadership with direction and motivation. Fourth, the control function includes evaluation and corrective action. Although in its implementation there are still obstacles such as the branding of institutions that are not well known, the collection side is still weak and efforts to re-strengthen the internal consolidation side of the institution. Manajemen fundraising merupakan kegiatan menghimpun dana Wakaf, infaq dan shodaqoh melalui proses perencanaan, pengorganisasian, kepemimpinan dan pengendalian dalam mencapai tujuan. Dalam kegiatan fundraising terdapat fungsi-fungsi manajemen dan langkah-langkah dalam menjalankan fungsi-fungsi tersebut. Secara tradisional, pekerjaan seorang manajer telah diuraikan menurut fungsi manajemen klasik, yaitu: merencanakan, mengorganisasikan, memimpin, dan mengendalikan. Perlu dipahami fungsi-fungsi manajemen dan langkah-langkah manajemen fundraising yang baik, diantaranya: Pertama, fungsi perencanaan yang meliputi perhitungan dan perkiraan masa depan, penentuan dan perumusan sasaran, penetapan metode, penetapan waktu dan lokasi, dan penetapan program, penetapan biaya. Kedua, fungsi pengorganisasian dalam pembagian tugas dan tanggung jawab, koordinasi antar pengurus serta relasi antarpengurus bagian. Ketiga, fungsi kepemimpinan dengan pengarahan dan motivasi. Keempat, fungsi pengendalian meliputi evaluasi dan tindakan koreksi. Meskipun dalam pelaksanaanya masih ada hambatan seperti branding lembaga yang kurang dikenal, sisi penghimpunan yang masih melemah serta usaha penguatan kembali dalam sisi konsolidasi internal lembaga.